Social and geographic inequalities in premature adult mortality in Japan: a multilevel observational study from 1970 to 2005 - Suzuki, Etsuji (BMJ Group, 2012)
OBJECTIVES: To examine trends in social and geographic inequalities in all-cause premature adult mortality in Japan. DESIGN: Observational study of the vital statistics and the census data. SETTING: Japan. PARTICIPANTS: Entire population aged 25 years or older and less than 65 years in 1970, 1975, 1980, 1985, 1990, 1995, 2000 and 2005. The total number of decedents was 984 022 and 532 223 in men and women, respectively. MAIN OUTCOME MEASURES: For each sex, ORs and 95% CIs for mortality were estimated by using multilevel logistic regression models with ‘cells’ (cross-tabulated by age and occupation) at level 1, 8 years at level 2 and 47 prefectures at level 3. The prefecture-level variance was used as an estimate of geographic inequalities of mortality. RESULTS: Adjusting for age and time-trends, compared with production process and related workers, ORs ranged from 0.97 (95% CI 0.96 to 0.98) among administrative and managerial workers to 2.22 (95% CI 2.19 to 2.24) among service workers in men. By contrast, in women, the lowest odds for mortality was observed among production process and related workers (reference), while the highest OR was 12.22 (95% CI 11.40 to 13.10) among security workers. The degree of occupational inequality increased in both sexes. Higher occupational groups did not experience reductions in mortality throughout the period and was overtaken by lower occupational groups in the early 1990s, among men. Conditional on individual age and occupation, overall geographic inequalities of mortality were relatively small in both sexes; the ORs ranged from 0.87 (Okinawa) to 1.13 (Aomori) for men and from 0.84 (Kanagawa) to 1.11 (Kagoshima) for women, even though there is a suggestion of increasing inequalities across prefectures since 1995 in both sexes. CONCLUSIONS: The present findings suggest that both social and geographic inequalities in all-cause mortality have increased in Japan during the last 3 decades.